UPAYA MENINGKATKAN KETERAMPILAN MENYIMAK SISWA MELALUIMEDIA REKAMAN DONGENG ANAK PADA SISWA KELAS IV SD - Harwati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The purpose of this study was to determine the efforts to improve students' listening skills through the media of children's fairytales recording at grade IV of SDN Banget 2, Kelurahan Kwadungan, Kabupaten Ngawi in the academic year of 2021/2022. The method used in this study was classroom action research. The results showed that appropriate andrelevant learning media increased students' understanding of the materials because students were directly involved in the learning process. By directly experiencing the learning process, students quickly understood the concept of learning materials. After applying recording media for children's fairy tales, the students' listening ability increased. It was proved by the increase in students' learning achievement through the evaluation, showing that the average score in the pre-cycle was 62.5, and it increased to 70 in the first cycle and 82 in the second cycle. This study suggested that as a key instrument of educational success, teachers should continually improve their pedagogical competence through several KKG activities, educational workshops or seminars, and training. Meanwhile, students must often practice listening to a story or a children's fairytale to comprehend the materials better.